Characterization of vacuum-packed sterilized biko as disaster food - Lim, Jadice J.; Gonzales, Benjamin A. (Quezon City College of Home Economics, University of the Philippines Diliman, 2018.)
In the Philippines, biko is one of the famous rice cakes eaten during festivals and special occasions. A prototype vacuum-packed sterilized biko obtained from a previous study was characterized for its suitability as a disaster food by conducting focus group discussions, consumer acceptance tests, and physico-chemical tests. The results of the focus group discussion showed that the prototype was fit for a disaster food as it is culturally acceptable, has long shelf-life, and requires no preparation. Nine point hedonic scale consumer acceptance test results indicate that the 4- and 8- week old prototypes obtained scores ranging from ―neither like nor dislike‖ (week 4 color, appearance, texture and overall acceptability) to ―like moderately‖ (week 8 sweetness and taste) and were significantly less acceptable compared to a commercial sample for color, appearance, texture, and overall acceptability. Physico-chemical tests comparing week 4 and 8 prototypes indicate no significant difference in pH (5.5233 vs. 5.500) and lower water activity (0.8133 vs. 0.8660) and L- (43.5067 vs. 45.3500), a- (8.9933 vs. 10.4300), b- (31.6600 vs. 33.4933) color for week 4. The study concludes that the final prototype of the vacuum-packed sterilized biko was deemed suitable as a disaster food by those affected by natural disasters even though the panellist from the consumer acceptance test found the commercially-available sample more acceptable.
Thesis (B.S. Food Technology)--University of the Philippines Diliman.
Keywords: Biko; Disaster food